절식이 나일 틸라피아 Oreochromis niloticus의 Kiss2, GnRH I mRNA 발현 및 성 스테로이드 호르몬 농도에 미치는 영향 - 박진우; 권준영; 진예화; 오승용; Park, Jin Woo; Kwon, Joon Yeong; Jin, Ye Hwa; Oh, Sung-Yong (Ocean and polar research, 2016)
In many fish species, including Nile tilapia (Oreochromis niloticus), gonadal development occurs at the expense of stored energy and nutrients. Therefore, reproductive systems are inhibited by limited food supply. It has been well established that reproductive function is highly sensitive to both metabolic status and energy balance. Nothing is known about the possible mediated connection between energy balance and reproduction. Kisspeptin, a neuropeptide product of the Kiss gene has emerged as an essential gatekeeper of reproduction and may be possibly be linked to energy balance and reproduction in non-mammalians. Thus, in this study, the effect of fasting (10 days) on the expression of kisspeptin and the gonadotropin-releasing hormone (GnRH) gene were assessed in Nile tilapia (male and female) using qRT-PCR. In addition, plasma levels of estradiol-$17β$ ($E_2$) and 11-ketotestosterone (11-KT) in adult tilapia were measured by ELISA. In male tilapia, fasting reduced Kiss2 and GnRH I mRNA expression in the brain and 11-KT level in comparison with the fed tilapia (p < 0.05). In females, however, there were no significant differences in GnRH I mRNA expression and $E_2$ between fish subjected to fasting and those fed (p > 0.05). These data indicate the impact of nutritional states on kisspeptin as a potential regulatory mechanism for the control of reproduction in male Nile tilapia.